The place of classical civilization in the school curriculum - Morton, Anne Caroline (Rhodes University, Faculty of Education, Department of Education, 1985)
Classical Studies, as a subject, has not been seriously presented in many schools until fairly recently. Britain initiated the introduction of Classical Studies to the school curriculum in 1974, and interest has continued to grow steadily in other countries like America, New Zealand, Australia and Canada. This thesis was started on the assumption that this entirely new subject could be introduced into the curriculum for standard six and seven pupils at South African schools, for reasons which will be given later. As work continued on the thesis, the 1985 syllabus for Latin lent it further impetus. Some of the implications of the new Latin syllabus will be considered in the conclusion (Introduction, p. 6)
Keywords: Education -- Curricula -- South Africa; Civilization, Classical -- Study and teaching; Latin language -- History -- 20th century; Latin language -- Study and teaching (Secondary) -- South Africa